Strontium ranelate in postmenopausal osteoporosis treatment: a critical appraisal - Roberto Cesareo; Clemente Napolitano; Mario Iozzino (Dove Medical Press, 2009)
Roberto Cesareo1, Clemente Napolitano1, Mario Iozzino21Department of Internal Medicine, 2Department of Radiology, S.M. Goretti Hospital, Latina, ItalyAbstract: Osteoporosis is a progressive and debilitating disease characterized by a massive bone loss with a deterioration of bone tissues, and a propensity for a fragility fracture. Strontium ranelate is the first antiosteoporotic treatment that has dual mode of action and simultaneously increases bone formation, while decreasing bone resorption, thus rebalancing bone turnover formation. Strontium ranelate rebalances bone turnover in favor of improved bone geometry, cortical thickness, trabecular bone morphology and intrinsic bone tissue quality, which translates into enhanced bone strength. This review describes the mechanism of the strontium ranelate action and its effects on bone mineral density, bone turnover, and osteoporotic fractures. The efficacy of strontium ranelate in postmenopausal osteoporosis treatment to reduce the risk of vertebral and hip fractures has been highlighted in several randomized, controlled trials. Treatment efficacy with strontium ranelate has been documented across a wide range of patient profiles: age, number of prevalent vertebral fractures, body mass index, and a family history of osteoporosis. Because strontium ranelate has a large spectrum of efficacy, it can be used to treat different subgroups of patients with postmenopausal osteoporosis. Strontium ranelate was shown to be relatively well tolerated and the safety aspects were good. Strontium ranelate should be considered as a first-line treatment for postmenopausal osteoporotic patients.Keywords: osteoporosis, strontium ranelate, therapy